THE EFFECT OF STUDENT CENTERED LEARNING APPROACH ON THE ABILITY TO IDENTIFY PLANTS IN THE FOREST OF EDEN PARK 100 IN BIOLOGY EDUCATION STUDENTS OF FKIP UISU MEDAN - Nurhasnah Manurung; Pandu Prabowo Warsodirejo (State Islamic University of North Sumatra Indonesia, 2019)
This study aims to determine whether there is the influence of Student Centered Learning approaches to the ability to identify plants in Taman Eden 100 forest in Biology Educations Students FKIP UISU Medan. This research was conducted in March – June 2018. This research used quasi Experiment method with research population is all college students Biology Educations FKIP UISU Medan which amounted to 103 students which then made as many as 21 students from Semester 4 Biology Educations by way of Non Probability Sampling technique with Purposive Sampling. The data analyzed in research is a written test that is pre test and post test on vegetation of plants material courses plant Ecology. The average value of pre test before applied the Student Centered Learning approaches is 50,21 and standard deviation 13,07 then as many good categories 3 people (14,28%) and 18 people including less categories (85,71%). And the average post test is obtained after the applied the Student Centered Learning approaches is 69,92 and standard deviation is 7,32 then students as many good categories is 14 people (67%) and 7 people including less categories (33%). Based on the hypothesis test obtained tcount = 6,92 while the value ttable = 1,72 so tcount > t table, thus Ha accepted and H0 rejected, and it can be concluded that there is significant effect of using the Student Centered Learning approaches to the ability to identify plants in Taman Eden 100 forest in Biology Educations College Students FKIP UISU Medan Keywords: Student Centered Learning Approach, Plants in the Forest of Eden Park100, Biology Education Students of FKIP UISU Medan